2023
DOI: 10.1007/s11060-023-04333-3
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic therapy and magnetic resonance-guided focused ultrasound: new therapeutic strategy in glioblastoma

Abstract: Glioblastoma (GB) is one of the most aggressive and difficult-to-treat brain tumors, with a poor prognosis and limited treatment options. In recent years, sonodynamic therapy (SDT) and magnetic resonance focused ultrasound (MRgFUS) have emerged as promising approaches for the treatment of GB. SDT uses ultrasound waves in combination with a sonosensitizer to selectively damage cancer cells, while MRgFUS delivers high-intensity ultrasound waves to precisely target tumor tissue and disrupt the blood–brain barrier… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 103 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…In several in vitro studies, efficacy of SDT was demonstrated via apoptotic effects and generation of ROS. Similar results have been shown by in vivo studies in animal models [ 4 , 24 , 33 , 38 , 39 ].…”
Section: Sonodynamic Therapy (Sdt)supporting
confidence: 89%
See 1 more Smart Citation
“…In several in vitro studies, efficacy of SDT was demonstrated via apoptotic effects and generation of ROS. Similar results have been shown by in vivo studies in animal models [ 4 , 24 , 33 , 38 , 39 ].…”
Section: Sonodynamic Therapy (Sdt)supporting
confidence: 89%
“…The duration of the intervention was 10 ms to 20 min. According to the known photosensitizers used for PDT, the following sonosensitizers have been analyzed: 5-ALA, fluorescein (FL), sinoporphyrin sodium (DVDMS), hematoporphyrin monomethyl ether (HMME), temozolomide (TMZ), and Photofrin [ 4 ]. Among these, 5-ALA is the most extensively studied sonosensitizer whose biocompatibility and biosafety have been widely demonstrated in clinical studies [ 7 ].…”
Section: Sonodynamic Therapy (Sdt)mentioning
confidence: 99%
“…The porcine model allows a more precise target definition, and better approaches human conditions [ 1058 ]. The efficacy of STD is limited in larger tumors because ultrasound waves cannot penetrate deep enough into the tumor [ 1059 ]. Three clinical trials are currently underway to evaluate the safety and feasibility of SDT with 5-ALA in patients with high-grade glioma (NCT04559685), in ndGBs using the ExAblate Model 4000 Type-2 Neuro System (NCT04845919), and the efficacy of SDT using SONALA-001 and Exablate Type-2 devices in subjects with rGB (NCT04988750).…”
Section: Non-ionizing Energies In Gb Therapymentioning
confidence: 99%
“…SDT combines focused ultrasound with sonosensitizers, which sensitize cells to sound-induced destruction, minimizing adverse events and maximizing target responses ( 48 , 55 ). Examples of sonosensitizers include 5-ALA, ATX-70, and Hypocrellin ( 56–58 ). The efficacy of SDT has been shown in studies by Sheehan et al, which demonstrated SDT’s efficacy in rat C6 and human U87 glioma cells by showing FUS and 5-ALA-induced cell death through ROS generation ( 59 ).…”
Section: Adjuncts To Fus In the Treatment Of Gliomamentioning
confidence: 99%
“…As a result, other studies have investigated the possibility of combining LIFUS with BBB modifiers, such as microbubbles, to increase the permeability of the BBB and improve SDT efficacy ( 64–66 ). Sonosensitizers used in Sonodynamic Therapy (SDT) comprise benign molecules that induce cytotoxic effects under an acoustic field ( 56 ). Several of these molecules are similar to those used in photodynamic therapy and are usually porphyrin-based or related compounds such as protoporphyrin IX and hematoporphyrin, among others.…”
Section: Adjuncts To Fus In the Treatment Of Gliomamentioning
confidence: 99%